Problematyka medycyny psychosomatycznej – od historii do współczesności = The issue of Psychosomatic Medicine – form history to nowadays - Tudorowska, Malwina (Journal of Education, Health and Sport, 2016)
Tudorowska Malwina. Problematyka medycyny psychosomatycznej – od historii do współczesności = The issue of Psychosomatic Medicine – form history to nowadays. Journal of Education, Health and Sport. 2016;6(6):121-134. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.54716 http://ojs.ukw.edu.pl/index.php/johs/article/view/3561 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. Problematyka medycyny psychosomatycznej – od historii do współczesności The issue of Psychosomatic Medicine – form history to nowadays Malwina Tudorowska Katedra Pielęgniarstwa Zachowawczego, Zakład Pielęgniarstwa Psychiatrycznego, Collegium Medicum w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu Department of Preventive Nursing, Institute of Psychiatric Nursing Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń Adres do korespondencji/Adress to correspondence: mgr Malwina Tudorowska Katedra Pielęgniarstwa Zachowawczego Zakład Pielęgniarstwa Psychiatrycznego Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy UMK w Toruniu, ul. Łukasiewicza 1, 85-821 Bydgoszcz tel.: (52) 585-58-22, tel./fax: (52) 585-58-49 e-mail: malwina.tudorowska@gmail.com Streszczenie U źródeł rozumienia medycyny psychosomatycznej znajdują się odniesienia do starożytnej myśli greckiej (Platon Hipokrates, Galen) na temat jedności i wzajemnych powiązań ciała i duszy. Początków rozwoju medyny psychosomatycznej upatruje się w latach 40. XX wieku. Wówczas domagano się spojrzenia na całego człowieka, na zdrowie i chorobę w perspektywie jego problemów psychologicznych i warunków środowiska. Pierwsi lekarze interesujący się zaburzeniami psychosomatycznymi, jak Franz Aleksander czy Flanders Dunbar, byli psychoanalitykami. Zwracali oni uwagę, że przyczyn chorób medycyna powinna poszukiwać przyczyn chorób nie tylko w czynnikach fizycznych, tj. drobnoustrojach, urazach czy niewłaściwych genach, ale także w cechach osobowości, utrwalonych sposobach zachowań czy traumach psychicznych. Rozwój tej dziedziny medycyny przyczynił się do obecnego rozumienia człowieka w sposób holistyczny zarówno w zdrowiu, jak i chorobie. Współczesna medycyna psychosomatyczna jest propozycją uprawiania medycyny klinicznej, a także promocji zdrowia i profilaktyki. Praca ma na celu przybliżenie rozwoju myślenia dotyczącego etiologii chorób i zaburzeń w kierunku poszukiwania syntez. Ważne jest również podkreślenie jak istotna jest współpraca medyków i psychologów w procesie diagnostycznym i leczniczym wielu schorzeń. Słowa kluczowe: medycyna psychosomatyczna, zaburzenia psychosomatyczne, psychoneuroimmunologia. Abstract At the source of the understanding of psychosomatic medicine are references to ancient Greek thought (Plato, Hippocrates, Galen) on the unity and interconnectedness of body and soul. The 40’s of the twentieth century are considered to be the beginning of the development of psychosomatic medicine. It was demanded to look at the whole human, on individual’s health and disease in the perspective of psychological problems and environmental conditions. The first physicians with an interest in psychosomatic disorders, such as Franz Alexander and Flanders Dunbar, were psychoanalysts. They pointed out that medicine should identify not only physical factors, like microorganisms, injuries or the wrong genes as the etiology of illnesses. Also personality traits, established ways of behavior or psychological trauma are important to take into consideration. Development of psychosomatic medicine has contributed to the current understanding of human in a holistic way, both in health and disease. Modern psychosomatic medicine is a proposal to practice clinical medicine as well as health promotion and prevention. The aim of this article is to present the thinking of the etiology of diseases and disorders in the direction of the search for synthesis. It is also important to emphasize the importance of cooperation medics and psychologists in the diagnostic process and healing of many diseases. Key words: psychosomatic medicine, psychosomatic disorders, psychoneuroimmunology.